Desain Mesin Pembuatan Gula Semut Berbahan Dasar Nira Kelapa Skala UMKM : - Munang, Aswan; Rachmawaty, Dina; Reza Basirun , Arif (Infotekmesin, 2023)
Product development is a combination of technological trends that play a role in creating innovative works. Conceptual design is the initial phase of developing innovative product configurations. The processing of coconut sap into traditional palm sugar has constraints; the production process takes 4 to 6 hours and has a moisture content above 3%. The research objective was to obtain a machine design to increase production volume and reduce the water content in palm sugar. The machine design process begins with conducting interviews with 20 palm sugar craftsmen with approximately 5 years of experience to obtain information on priority needs. The VOC (Voice Of Customer) method can be used to determine priority designs and specifications. The results of the VOC process are (1) machine components made of food-grade materials, (2) production machines that are easy to operate and easy to maintain, (3) production machines with operational costs and affordable prices among MSMEs. The design development process has two alternative machines made using the Solidworks software. The results of the assessment of 30 SMEs’ palm sugar selected alternative two machine designs with dimensions of 70 x 60 x 155 cm. The advantage of the second engine design alternative is that it has a temperature sensor to adjust the gas valve and a pan with an insulator so that it can maintain temperature stability. The design of the palm sugar machine still requires innovation and development to increase production and quality.